To study the clinical, radiological and functional outcome of antibiotic mixed cement coated nails in infected long bone diaphyseal fractures - Uikey, Suresh; Kumar Oddam, Vinay; Verma, Rahul (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Background: In Present Era, High velocity trauma are common trends leading to compound long bone fractures. These fractures have high chance of infection which further leads to infected non-union. Traditionally multistage procedure such as debridement and systemic antibiotics with temporary fixation and then permanent fixation and bone grafting when required. Single staged procedures such as debridement and application of Ilizarov fixator and limb reconstruction system are also available. Recently, development ofinfection control by local antibiotic delivery systems, initially antibiotic cement beads then antibiotic cement impregnated intramedullary nail (ACIINs).The aim of this study is to analyze clinical, functional and radiological outcome of antibiotic mixed cement coated nailing in infected long bone diaphyseal fractures. Material and Methods: In our prospective study, 20 patients of 17-70 years of age group with infected long bone diaphyseal fractures were treated using antibiotic mixed cement coated intramedullary nails. The outcome of study was analyzed for infection control, radiological sign of union, ability to bear weight and patient compliance. Results: In our study, we achieved infection control in 95% of patients with complete radiological union in 50% of cases with ability to bear weight without pain. Conclusion: Antibiotic Mixed Cement Coated Nailing was a good procedure to achieve infection control, provide stability and bone union in infected long bone fractures.